VERTICALIZATION, EXPANSION, AND EPISTEMOLOGICAL DISPUTES IN PROFESSIONAL EDUCATION: THE TRAJECTORY OF IF GOIANO – MORRINHOS CAMPUS AND THE CHALLENGES OF INTEGRATED HIGH SCHOOL EDUCATION AS STATE POLICY - Felippe, José Neto de Oliveira (Seven Editora, 2026)
This study investigates the institutional trajectory of the former Federal Agrotechnical School of Morrinhos until its consolidation as the Federal Institute of Goiás – Morrinhos Campus, examining how this journey expresses political, pedagogical, and epistemological disputes in the field of Professional and Technological Education (EPT) in Brazil. The objective is to analyze this trajectory in light of the consolidation of PTE as a public policy of the State, the permanence of educational duality, and the influence of market rationalities, in addition to highlighting advances in the verticalization and diversification of the institution's educational offerings. To this end, we conducted documentary research and content analysis guided by a critical theoretical framework, based on institutional, regulatory, and academic sources. The results indicate that, although the creation of Federal Institutes represents progress in democratizing access to public education and in the internalization of VET, structural challenges related to curricular fragmentation and managerial pressures persist. It is evident that Integrated Secondary Education is a space of contention between antagonistic educational projects, strained by reforms that compromise its emancipatory proposal. An analysis of the current course offerings at the Morrinhos Campus —which range from technical training to stricto sensu graduate programs —reinforces the institution's strategic role in building an integrated, omnilateral, and socially referenced educational project. It can be concluded that the experience analyzed reflects the advances and contradictions of EFA as a political field in constant dispute.DOI: https://doi.org/10.56238/sevened2026.008-051